2014
DOI: 10.5539/ass.v10n5p155
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Motor Skill among 6-Year-Old Children in Padang, West Sumatera, Indonesia

Abstract: This study examined 6 year-old children's fundamental motor skills. Participants were 67 first grade elementary students in rural and urban area in Padang, West Sumatera, Indonesia. All participants were evaluated with the Test of Gross Motor Development-2 (TGMD-2) (Ulrich, 2000). Boys were slightly higher in both locomotor and manipulative skills, yet there were no gender differences for both skills. Children in the average fundamental motor skills group is more in the rural area as compared to urban areas. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
3
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 14 publications
6
43
3
5
Order By: Relevance
“…Most studies were conducted in the USA [ 18 , 22 , 51 , 53 , 58 , 61 63 , 66 , 82 , 87 ] and Australia [ 33 , 49 , 50 , 70 , 75 , 76 , 95 , 96 , 98 , 100 ]. A total of 21 studies were conducted across Europe (Belgium [ 71 73 , 90 , 91 ], Finland [ 48 , 88 , 97 , 99 ], Portugal [ 19 , 64 , 80 ], Denmark [ 59 , 84 ], Greece [ 89 , 93 ], Germany [ 101 ], Ireland [ 81 ], Italy [ 57 ], Northern Ireland [ 83 ] and Norway [ 92 ]), eight in Asia (Hong Kong [ 52 , 55 , 69 ], Bangladesh [ 85 ], India [ 67 ], Indonesia [ 68 ], Japan [ 54 ] and Pakistan [ 74 ]), five in Canada [ 56 , 65 , 77 , 79 , 94 ], two in Brazil [ 23 , 60 ] and a single study each from Israel [ 86 ] and South Africa [ 78 ]. Most study designs were cross-sectional [ 18 , 19 , 22 , 23 , 33 , 49 , 5...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were conducted in the USA [ 18 , 22 , 51 , 53 , 58 , 61 63 , 66 , 82 , 87 ] and Australia [ 33 , 49 , 50 , 70 , 75 , 76 , 95 , 96 , 98 , 100 ]. A total of 21 studies were conducted across Europe (Belgium [ 71 73 , 90 , 91 ], Finland [ 48 , 88 , 97 , 99 ], Portugal [ 19 , 64 , 80 ], Denmark [ 59 , 84 ], Greece [ 89 , 93 ], Germany [ 101 ], Ireland [ 81 ], Italy [ 57 ], Northern Ireland [ 83 ] and Norway [ 92 ]), eight in Asia (Hong Kong [ 52 , 55 , 69 ], Bangladesh [ 85 ], India [ 67 ], Indonesia [ 68 ], Japan [ 54 ] and Pakistan [ 74 ]), five in Canada [ 56 , 65 , 77 , 79 , 94 ], two in Brazil [ 23 , 60 ] and a single study each from Israel [ 86 ] and South Africa [ 78 ]. Most study designs were cross-sectional [ 18 , 19 , 22 , 23 , 33 , 49 , 5...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies used process-oriented assessments. The most commonly used was the Test of Gross Motor Development (TGMD): first edition, three studies [ 53 , 57 , 66 ] and second edition, 15 studies [ 22 , 23 , 49 , 50 , 52 , 56 , 60 , 62 , 63 , 65 , 68 70 , 88 , 89 ]. Australian resources were used in six studies (Department of Education Victoria [ 75 , 98 , 100 ] and Get Skilled Get Active [ 33 , 76 , 96 ]; three studies each).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Sularyo and Akhib in Lombok, Indonesia, demonstrated that most children were delayed in their gross-motor skills, social, language and fine motor development, with these delays increasing across age [13]. Along with this data, some studies in elementary school students in West Sumatera found that elementary school students were delayed on their low motor competence [18,19]. Such data may contribute to increasing sedentary lifestyles among adolescence that leads to an increase in overweight and obesity.…”
Section: Introductionmentioning
confidence: 81%
“…folding, cutting papers, drawing and patching appropriate pictures). Another preliminary study in ECE centers in Padang city shows that children at age 3 -5 years showed low competence on their fundamental motor skills [11] [12].…”
Section: Introductionmentioning
confidence: 99%